A Mathematical Model for Determining Carbon Coating Thickness and Its Application in Electron Probe Microanalysis - Zhang, Ruo-Xi; Yang, Shui-Yuan (Microscopy and microanalysis, 2016)
In electron probe microanalysis where materials are coated with a thin conductive carbon coat before analysis, the X-ray intensity detected from a specimen may be affected to various degrees by the thickness of the carbon coating. Differences in the carbon film thickness between specimens and standards may lead to errors in analytical results, particular for lower energy X-rays. In this study, we demonstrate that the location and the distance of the specimen relative to the carbon tip in the coating chamber can affect the thickness of the carbon film produced on the specimen surface during carbon coating. The closer the specimen is to the carbon tip contacting point, the thicker is the carbon film deposited. A mathematical model to calculate the carbon film thickness at different locations on the coater plate is established, based on the assumption that carbon atoms evaporate from the carbon tip equally in all directions during the coating process. In order to reduce the differences in the carbon coating thickness, we suggest moving the carbon rod to a higher position, moving the thinner samples to the center and thicker samples to the edge of the coater plate, and using a rotating circular coater plate during coating.